PERUBAHAN LAHAN TAMBANG BATU BARA DI KECAMATAN PERANAP, KABUPATEN INDRAGIRI HULU TAHUN 2016, 2019 DAN TAHUN 2022 - Raihan Mulyana; Dwi Marsiska Driptufany; Fajrin Fajrin; Defwaldi Defwaldi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Coal mines in Peranap district are mined using the Open Cut Mining method, namely open pit mining. Open pit mining is one of two well-known mining systems, namely open pit mining and underground mining. Coal mining in the Peranap district began to be active in 2014 and is still active today. From 2014 until now there has been an increase in mining every year, both on land that has been cleared and land that is still new. This study aims to determine changes in coal mining land cover in Peranap District, Indragiri Hulu Regency through visual interpretation of remote sensing data. The remote sensing data used is Landsat 8 OLI imagery for 2016, 2019 and 2022. Furthermore, classifying satellite imagery using the Supervised Classification method. Based on the results of processing satellite imagery in 2016, the area covered by coal mining land is 12,3 Ha. The area of ​​coal mining land cover in 2019 is 44,7 Ha. Meanwhile, the area covered by coal mining land in 2022 is 51,1 hectares. Based on the results of the area of ​​coal mining land from 2016 to 2019, the area of ​​coal mining land cover has increased by 32,4 Ha. From 2019 to 2022, the area of ​​coal mining land cover has increased by 6,4 hectares. And from 2016 to 2022 the area of ​​coal mining land cover has increased by 38,8 hectares.